Joel and Rollin at Stanford - Pickford, Joel:::::::::
Joel and Rollin at Stanford. After completing two years at Fresno State, Rollin transferred to Stanford and graduated in 1933. However, he always said that he had better art teachers at Fresno State, including John Ed Herbert and Alexandra Bradshaw. One of Rollin's Fresno High School and Fresno State classmates, Frank Thomas, went on to become a famous Disney animator, working on Fantasia and other Disney feature films.